Can today's standardized achievement tests yield instructionally useful data?. Issue 4 (26th August 2014) - Madhabi Chatterji, Prof.; James Popham, W.; C. Berliner, David; M. Kingston, Neal; H. Fuhrman, Susan; M. Ladd, Steven; Charbonneau, Jeffrey; Chatterji, Madhabi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Against a backdrop of high-stakes assessment policies in the USA, this paper explores the challenges, promises and the "state of the art" with regard to designing standardized achievement tests and educational assessment systems that are instructionally useful. Authors deliberate on the consequences of using inappropriately designed tests, and in particular tests that are insensitive to instruction, for teacher and/or school evaluation purposes. Methodology/approach – The method used is a "moderated policy discussion". The six invited commentaries represent voices of leading education scholars and measurement experts, juxtaposed against views of a prominent leader and nationally recognized teacher from two American education systems. The discussion is moderated with introductory and concluding remarks from the guest editor, and is excerpted from a recent blog published by Education Week. References and author biographies are presented at the end of the article. Findings – In the education assessment profession, there is a promising movement toward more research and development on standardized assessment systems that are instructionally sensitive and useful for classroom teaching. However, the distinctions among different types of tests vis-à-vis their purposes are often unclear to policymakers, educators and other test users, leading to test misuses. The authors underscore issues related to validity, ethics and consequences when inappropriately designed tests are used in high-stakes policy contexts, offering recommendations for the design of instructionally sensitive tests and more comprehensive assessment systems that can serve a broader set of educational evaluation needs. As instructionally informative tests are developed and formalized, their psychometric quality and utility in school and teacher evaluation models must also be evaluated. Originality/value – Featuring perspectives of scholars, measurement experts and educators "on the ground", this article presents an open and balanced exchange of technical, applied and policy issues surrounding "instructionally sensitive" test design and use, along with other types of assessments needed to create comprehensive educational evaluation systems.